2017
DOI: 10.1016/j.ygyno.2017.03.004
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of outcomes for MR-guided versus CT-guided high-dose-rate interstitial brachytherapy in women with locally advanced carcinoma of the cervix

Abstract: Objective The purpose was to compare local control (LC), overall survival (OS) and dose to the organs at risk (OAR) in women with locally advanced cervical cancer treated with MR-guided versus CT-guided interstitial brachytherapy (BT). Methods 56 patients (29 MR, 27 CT) were treated with high-dose-rate (HDR) interstitial BT between 2005–2015. The MR patients had been prospectively enrolled on a Phase II clinical trial. Data were analyzed using Kaplan-Meier (K-M) and Cox proportional hazards statistical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Concurrent chemoradiotherapy (CCRT) is considered the primary treatment of choice for Stage IB2‐IVA uterine cervical squamous cell carcinoma based on randomized clinical trials and meta‐analyses . Recent studies have shown that CCRT and image‐guided brachytherapy improve the clinical outcome of patients with cervical carcinoma, especially squamous cell carcinoma . Conversely, few studies have investigated treatment options for adenocarcinomas; these are typically treated in a similar manner to squamous cell carcinomas .…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent chemoradiotherapy (CCRT) is considered the primary treatment of choice for Stage IB2‐IVA uterine cervical squamous cell carcinoma based on randomized clinical trials and meta‐analyses . Recent studies have shown that CCRT and image‐guided brachytherapy improve the clinical outcome of patients with cervical carcinoma, especially squamous cell carcinoma . Conversely, few studies have investigated treatment options for adenocarcinomas; these are typically treated in a similar manner to squamous cell carcinomas .…”
Section: Introductionmentioning
confidence: 99%
“…This is worrying since it correlates to inferior local control [ 4 ]. In fact, recently published data comparing MRI-guided versus CT-guided brachytherapy shows inferior overall survival for patients with CT-guided brachytherapy, which could possibly be explained by the results of the current study [ 21 ]. Five out of 11 of CT-guided plans had HRCTV mri D 90 higher than 8.3 Gy, extrapolated to total biological equivalent dose of more than 95 Gy.…”
Section: Discussionmentioning
confidence: 73%
“…Published clinical data show favourable local control using this technique . Kamran et al . compared outcomes of MR‐guided versus CT‐guided brachytherapy and found that patients treated with MR‐guided brachytherapy had excellent toxicity rates, although was similar to CT‐guided brachytherapy, likely due to similar brachytherapy prescription dose between groups (35 Gy for each).…”
Section: Discussionmentioning
confidence: 99%